First Documented Case of Percutaneous Endoscopic Gastrostomy (PEG) Tube-Associated Bacterial Peritonitis due to Achromobacter Species with Literature Review. (16th January 2020) - Tripathi, Nishant; Koirala, Niki; Kato, Hirotaka; Singh, Tushi; Karri, Kishore; Thakur, Kshitij
Abstract : Introduction. Achromobacter species (spp.) peritonitis has seldom been identified in medical literature. Scarce cases of Achromobacter peritonitis described previously have been correlated with peritoneal dialysis and more sparingly with spontaneous bacterial peritonitis. Achromobacter exhibits intrinsic and acquired resistance, especially in chronic infections, to most antibiotics. This article conducts a literature review of all previously reported Achromobacter spp. peritonitis and describes the first reported case of Achromobacter peritonitis as a complication of percutaneous endoscopic gastrostomy (PEG) tube placement. Discussion. Achromobacter peritonitis as a complication of PEG-tube placement has not been previously reported. In our patients' case, the recently placed PEG-tube with ascitic fluid leakage was identified as the most plausible infection source. Although a rare bacterial peritonitis pathogen, Achromobacter may be associated with wide antimicrobial resistance and unfavorable outcomes. Conclusion. No current guidelines provide significant guidance on treatment of PEG-tube peritonitis regardless of microbial etiology. Infectious Disease Society of America identifies various broad-spectrum antibiotics targeting nosocomial intra-abdominal coverage; some of these antimicrobial selections (such as cefepime and metronidazole combination) may yet be inadequate for widely resistant Achromobacter spp. Recognizably, the common antibiotics utilized for spontaneous bacterial peritonitis, i.e., third generation cephalosporins and fluoroquinolones, to which Achromobacter is resistant and variably susceptible, respectively, would be extensively insufficient. Piperacillin/tazobactam (P/T) and carbapenem were identified to provide the most reliable coverage in vitro ; clinically, 5 out of the 8 patients who received either P/T or a carbapenem, or both, eventually experienced clinical improvement.